Identification and characterization of promoters and cis-regulatory elements of genes involved in secondary metabolites production in hop (Humulus lupulus. L). (October 2016) - Duraisamy, Ganesh Selvaraj; Mishra, Ajay Kumar; Kocabek, Tomas; Matoušek, Jaroslav
Graphical abstract: Highlights: Single or combination of different cis -acting regulatory elements involved in the transcriptional regulation metabolic genes involved in biosynthesis of prenylflavanoid (PF) and bitter acid (BA) production in Humulus lupulus . The presence of hormonal and stress responsive cis -acting regulatory elements, indicates their putative role in co-regulation of PF and BA biosynthesis in hop. The in-depth knowledge of involvement of cis -acting regulatory elements in transcriptional control of PF and BA biosynthesis would assist to improve biological research in hop for pharmacological application. Abstract: Molecular and biochemical studies have shown that gene contains single or combination of different cis -acting regulatory elements are actively controlling the transcriptional regulation of associated genes, downstream effects of these result in the modulation of various biological pathways such as biotic/abiotic stress responses, hormonal responses to growth and development processes and secondary metabolite production. Therefore, the identification of promoters and their cis -regulatory elements is one of intriguing area to study the dynamic complex regulatory network of genes activities by integrating computational, comparative, structural and functional genomics. Several bioinformatics servers or database have been established to predict the cis -acting elements present in the promoter region of target gene and their association with the expression profiles in the TFs. The aim of this study is to predict possible cis -acting regulatory elements that have putative role in the transcriptional regulation of a dynamic network of metabolite gene activities controlling prenylflavonoid and bitter acids biosynthesis in hop ( Humulus lupulus ). Recent release of hop draft genome enabled us to predict the possible cis -acting regulatory elements by extracting 2 kbp of 5′ regulatory regions of genes important for lupulin metabolome biosynthesis, using Plant CARE, PLACE and Genomatix Matinspector professional databases. The result reveals the plausible role of cis -acting regulatory elements in the regulation of gene expression primarily involved in lupulin metabolome biosynthesis including under various stress conditions.